سيمياء التّناصّ في نونيّة أبي البقاء الرُّنديّ /The semiotic of intertextuality in the Nuniyyah poem of Abu al-Buqā’ al-Rundi - Hayam Abdul Karim al-Mammari (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: يسعى البحث إلى مقاربة النّصّوص العربيّة القديمة مقاربة تثبت ما تتمتّع به من إمكانيّات عدّة، تسمح بدراستها ضمن مناهج ورؤى متعدّدة، في ضوء النّظريّة النّقديّة واللّغويّة الحديثة، ويطبّق ذلك على قصيدة "أبي البقاء الرُّنديّ" بمطلعها: "لكلّ شيءٍ إذا ما تَمَّ نُقصانُ.... فلا يُغَـرّ بطيبِ العَيشِ إنسانُ"؛ لاستشراف آفاق جديدة في دراسة هذا النّصّ العربيّ القديم المتجدّد، مقاربة سيميائيّة وتناصّيّة حديثة؛ تروم سبر غوره، وما يمور فيه من ثنائيّات، وتضادّ، ومقابلات، وتكشف كيفيّة توظيف اللّغة الشّعريّة فيه، بكلّ ما تزخر به من بديع وطواعية واتّساق. وتوصّل البحث إلى أنّ هذه القصيدة تتبع في نهجها القصيدة العربيّة القديمة؛ في السّبك والنّظم، والهيكل الخارجيّ وغيره، وتعدّ من أشهر قصائد الاستصراخ ورثاء الممالك، كما لوحظ تحقّق الثّنائيّات في فضاء النّصّ، وإمكانيّة تطبيق "مربّع جريماس السّيميائيّ" في كثير من المواضع، وبرزت الحقول الدّلاليّة واضحة كذلك، وجاء التّكرار ليقوّي شوكة المعنى، ويؤكّد عمق الدّلالة، وعزّز ذلك كلّه حضور سيميائيّة الثّقافة، وسيميائيّة التّواصل. الكلمات المفتاحيّة: نونيّة الرُّنديّ-رثاء الممالك-التّناصّ-عتبات النّصّ-السّيميائيّة. Abstract The study tries to approach Arabic traditional texts in a manner that would open broader possibilities that would allow them to be studied through different methods and perspectives in the light of modern critical and linguistic theory. In this regard the poem of Abu al-Baqa’ al- Rundi which has the opening of the verse: “For everything when its shortcoming is completed..that a person cannnot be blessed with a comfortable living”, will be studied in a new perspective through modern semiotic, intertextual approach. This is in order to explore it deeper by looking into its dualities, antonyms, synonyms and the means through which they were employed in the text and with all the tools through which they appear through creative, symmetrical and cohesive expressions. The study found that the poem was in the traditional format in its structure and was considered one of the best of elegy for the Memluk. It was also concluded the presence of dualities in the content of the text and the possibility of applying the Greimas semiotic square in many places. The semantic fields were also clear, repetition was used to emphasize meaning and the depth of it. In addition to that the semiology of culture and communication was also present. Keywords: Nuniyyah of al-Rundi, elegy of the Memluks, intertextuality, the obstacles of the text, Semiology Abstrak Kajian in icuba untuk mengkaji teks tradisional Arab dengan cara yang dapat membuka lebih banyak kemungkinan yang membolehkan teks-teks sedemikian untuk dikaji melalui metod dan sudut pandangan yang berbeza dalam konteks teori kritikan sastera dan linguistik moden. Dalam hal ini, syair Abu al-Baqā’ al-Rundi yang permulaannya ialah: “Sesuatu yang kekurangannya telah sempurna..maka seseorang itu tidak kan dikurnia kehidupan yang senang”, akan dijadikan kajian melalui satu pendekatan baru dengan pendekatan semiotik dan intertekstual. Ini adalah untuk melihat dengan lebih mendalam melalui pasangan kata, kata berlawanan, kata seerti juga cara semua ini diserlahkan di dalam teks dan ungkapan-ungkapan lain yang kreatif, selari dan berkesinambungan. Kajian ini mendapati syair ini adalah dalam bentuk yang tradisional dan dianggap satu daripada syair ratapan di zaman Mamluk. Kewujudan pesangan perkataan dalam kandungan teks tersebut dan kemungkinan penerapan analisa empat segi semiotic Greimas di banyak tempat. Lapangan semantiknya juga nampak amat jelas, pengulangan digunakan untuk menekankan makna dan kedalamannya. Ini juga turut diperkukuhkan dengan kehadiran simbol budaya dan komunikasi di dalam teks tersebut. Kata kunci: Nuniyyah al-Rundi, ratapan era Memluk, intertekstualiti, halangan-halangan teks, semiology.